Lipoprotein sialylation in atherosclerosis: Lessons from mice - Yu, Liming; Peng, Jun; Mineo, Chieko (Frontiers in Endocrinology, 2022)
Sialylation is dynamically regulated modification, which commonly occurs at the terminal of glycan chains in glycoproteins and glycolipids in eukaryotic cells. Sialylation plays a key role in a wide array of biological processes through regulation of protein-protein interactions, intracellular localization, vesicular trafficking and signal transduction. Majority of the proteins involved in lipoprotein metabolism and atherogenesis, such as apolipoproteins and lipoprotein receptors, are sialylated in their glycan structures. Earlier studies in humans and in preclinical models found a positive correlation between low sialylation of lipoproteins and atherosclerosis. More recent works using loss- and gain-of-function approaches in mice have revealed molecular and cellular mechanisms by which protein sialylation modulates causally the process of atherosclerosis. The purpose of this concise review is to summarize these findings in mouse models and to provide mechanistic insights into lipoprotein sialylation and atherosclerosis.